2013
DOI: 10.1021/ja4013485
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Highly Crystalline MoS2 Flakes by Chemical Vapor Deposition

Abstract: The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for the practical applications of this emerging material. Here, we developed an approach for synthesizing MoS2 flakes in rhomboid shape with controlled number of layers by the layer-by-layer sulfurization of MoO2 microcrystals. The obtained MoS2 flakes showed high crystallinity with crystal domain size of ~10 μm, significantly larger than the grain size of MoS2 grown by other methods. As a result of the high crystallinity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

57
584
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(643 citation statements)
references
References 34 publications
57
584
0
2
Order By: Relevance
“…The Mo 3 d 3/2 and 3 d 5/2 peaks are located at ≈230.0 and ≈233.2 eV, respectively, while the S 2 p 1/2 and S 2 p 3/2 peaks are located at ≈164.0 and ≈162.9 eV, respectively. These peak positions are consistent with the reported values for 2H‐MoS 2 crystals 34. The positions of the Mo peaks indicate the reduction of Mo from Mo 6+ (MoO 3 ) to Mo 4+ (MoS 2 ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The Mo 3 d 3/2 and 3 d 5/2 peaks are located at ≈230.0 and ≈233.2 eV, respectively, while the S 2 p 1/2 and S 2 p 3/2 peaks are located at ≈164.0 and ≈162.9 eV, respectively. These peak positions are consistent with the reported values for 2H‐MoS 2 crystals 34. The positions of the Mo peaks indicate the reduction of Mo from Mo 6+ (MoO 3 ) to Mo 4+ (MoS 2 ).…”
supporting
confidence: 90%
“…Among these methods, chemical vapor deposition (CVD) is most promising in terms of scalability, simple operation and low cost, and has been used to grow various 2D materials directly on dielectric substrates 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. However, similar to other TMDs,19, 20, 21 CVD‐grown continuous MoS 2 film suffer from a high density of rotational domain boundaries 27, 28.…”
mentioning
confidence: 99%
“…CVD‐grown graphene has made great breakthrough in the growth of large‐area graphene 17, 155, 156, 157, 158, 159, 160. Recently, the synthesis of 2DLMs via CVD methods has been illustrated in many reports especially for MoS 2 ,30, 31, 161, 162, 163, 164, 165, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179, 180, 181, 182, 183, 184, 185 which also shows promising applications in electronics and optoelectronics. Up to now, there are several reports on synthesizing 2D GIVMCs nanoflakes via CVD method, which is still at the initial stage.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…The substrates were placed in a cold zone at 650 • C [46]. Feng et al [52] have also reported the synthesis of uniformly distributed monolayer MoS 2(1−x) Se 2x alloys on SiO 2 /Si substrates through the direct evaporation of MoSe 2 [44], (d,e) adapted with permission from Li et al [45], (f ,g) adapted with permission from Wu et al [46] and (h) adapted with permission from Liu et al [47].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%